(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
The main objective of this research is to investigate the characteristics of the treasury management in companies that constitute the Association of Municipalities of the Coal Region - AMCR - of the state of Santa Catarina.To reach this goal, a descriptive qualitative and quantitative research was conducted, through a closed questionnaire answered by 192 companies by accessibility. The results showed that most companies: a) are of a legal nature - Inc.; b) act in the area of trade and services; c) are micro and small; d) have appropriate treasury management practices of short-term; e) have few investments and loans in the financial market; f) carries out financing for vehicles, machinery and equipment; and g) capture resources in multiple/commercial banks and development banks. It can be concludedthat the surveyed companies have adequate organizational treasury management situation of short-term; however, many companies, regarding the long-term treasury activities,do not conduct budgeted/performed controls with financial planning and investment policies, loans and financing.This situation represents an important weakness of financial management, highlighting that some organizations do not have long-term view.